Cold plasma synthesis of Zinc Selenide Nanoparticles for inhibition bacteria using disc diffusion - Mazhir, Sabah N.; Abdalameer, Nisreen Kh.; Yaaqoob, Laith A.; Hammood, Jwan Kh. (Physics and Chemistry of Solid State, 2022)
Zinc Selenide Nanoparticles (NPs) were fabricated by the aqueous techneque using cold plasma under atmospheric pressure with an exposure time of 3 min and a gas flow rate of 3 liters per minute. films' structural characteristics and morphological characterization were investigated by X-ray diffract meter, atomic force microscopy (AFM), and scanning electron microscopy (FE-SEM). In addition, parameter like crystal size were calculated. Results showed XRD patterns exhibits structure of polycrystalline of preferential orientation (111) direction. SEM technique shows that the nanoparticles presented are spherical. AFM image verified film formed spherical particles distribute uniformly. The antibacterial disc diffusion property of these Nanoparticles, was performed against Gram-negative bacteria of Escherichia coli and Gram-positive bacteria of Staphylococcus aureos, showing good control of said bacteria. The maximum level of inhibition in coli form bacteria with an average inhibition zone diameter with stapheloscous aureous, implying an increasing trend with increasing/decreasing loading volume of NC volume. Therefore, these nanomaterials, which can be prepared in a simple and cost-effective way, may be suitable for new types of germicidal materials.